CASE STUDIES OF ILLEGAL, UNREPORTED AND UNREGULATED FISHING (IUU-F) IN HULU SUNGAI TENGAH REGENCY OF INDONESIA - Mahyudin I.; Hidayat A.S.; Rahmayani N. (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
Hulu Sungai Tengah Regency is a very strategic area for fishing activities. Usually people of Hulu Sungai Tengah fishing with various tools used, from traditional to modern tools. Starting from the tools that are allowed to be used to the tools that are prohibited. One of the tools that people are prohibited from using to catch fish is a stun. This tool is prohibited because it can cause damage to aquatic ecosystems. This condition cause’s people to take unlawful actions called Illegal, unreported and unregulated fishing. This study aims to analyze case studies of illegal, unreported and unregulated fishing (IUU-F) in Hulu Sungai Tengah Regency. This research was conducted in the fisheries area of Hulu Sungai Tengah Regency, South Kalimantan Province. Case studies of illegal, unreported and unregulated fishing (IUU-F) in Hulu Sungai Tengah Regency in the last 5 years during 2015-2020 there were 13 cases of IUU-Fishing found. This condition is continuous with the allocation of funds provided by the HST Regency government for PNS patrols, non-PNS patrols, Polairud and Pokmaswas.